2020
DOI: 10.7554/elife.54201
|View full text |Cite
|
Sign up to set email alerts
|

Boosts in brain signal variability track liberal shifts in decision bias

Abstract: Adopting particular decision biases allows organisms to tailor their choices to environmental demands. For example, a liberal response strategy pays off when target detection is crucial, whereas a conservative strategy is optimal for avoiding false alarms. Using conventional time-frequency analysis of human electroencephalographic (EEG) activity, we previously showed that bias setting entails adjustment of evidence accumulation in sensory regions (Kloosterman et al., 2019), but the presumed prefrontal signatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…By calculating entropy for patterns of different lengths (“multiscale”), the contributions of slower and faster timescales in the signal can be assessed. However, the mapping between entropy timescales and spectral frequencies is not absolute, especially since entropy is not per se related to a signal being oscillatory in nature (Kloosterman, Kosciessa, Lindenberger, Fahrenfort, & Garrett, 2020; Kosciessa et al, 2020). The advantage of using MSE is that it does not require filtering of the data, and it does not assume stationarity (e.g., it can pick up on regularities that are asymmetrical, or that do not have a fixed amplitude or period).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By calculating entropy for patterns of different lengths (“multiscale”), the contributions of slower and faster timescales in the signal can be assessed. However, the mapping between entropy timescales and spectral frequencies is not absolute, especially since entropy is not per se related to a signal being oscillatory in nature (Kloosterman, Kosciessa, Lindenberger, Fahrenfort, & Garrett, 2020; Kosciessa et al, 2020). The advantage of using MSE is that it does not require filtering of the data, and it does not assume stationarity (e.g., it can pick up on regularities that are asymmetrical, or that do not have a fixed amplitude or period).…”
Section: Methodsmentioning
confidence: 99%
“…A section of samples is considered a match if it resembles the template pattern enough to fall within a set boundary, which is defined as r x SD (the similarity bound). The number of pattern matches is counted. Subsequently, the same procedure is followed for patterns of m + 1 samples long. For the total counts of pattern matches throughout the time series, sample entropy is then calculated as the logarithm of the ratio between pattern matches of length m and pattern matches of length m + 1. Thus, sample entropy reflects the proportion of patterns in the time series that stays similar when an extra sample is added to the pattern. Here, we used m = 2 and r = 0.5, as was done previously for EEG data (Kloosterman, Kosciessa, Lindenberger, Fahrenfort, & Garrett, 2020).…”
Section: Supplementary Methods: Mse Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such models separate non-decision (e.g., motor) from decision-related components (e.g., rate of evidence accumulation, or drift rate ) and can also estimate the extent to which participants tend towards certain choice alternatives. Recent work suggests that those who can modulate evidence accumulation with increasing cognitive demand 30 and adjust their decision criteria when required also express greater EEG-based variability 31 . However, spatially specific (especially striato-thalamic) signatures of how neural variability reflects evidence accumulation and decision criteria under cognitive load remain unknown.…”
mentioning
confidence: 99%
“…This process can of course be willfully biased by the decision-maker, for example by adopting a liberal or conservative response criterion under differing task demands. For example, Kloosterman et al (2019) found that liberal response criteria are associated with a suppression of alpha band activity, relative to conservative criteria, which appears to systematically bias the direction of evidence accumulation toward a “target present” response in a go/no-go task (see also: Kloosterman et al, 2020 ). But given the logic of the DDM, influencing neural activity through explicit task demands is only one method of introducing systematic bias into the decision-making process, and other mechanisms may be external to the cognitive dynamics of evidence accumulation entirely.…”
Section: The Mddm: How Motor Costs Can Influence Decision-makingmentioning
confidence: 99%